2022
DOI: 10.1007/s00432-022-04088-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects and duration of exercise-based prehabilitation in surgical therapy of colon and rectal cancer: a systematic review and meta-analysis

Abstract: Purpose Functional capacity is an independent indicator of morbidity in colon and rectal cancer surgery. This systematic review describes the evaluated and synthesized effects of exercise prehabilitation depending on the duration of interventions on functional and postoperative outcomes in colon and rectal cancer surgery. Methods Three electronic databases (MEDLINE Pubmed, Web of Sciences, and Cochrane Registry) were systematically searched (January 2022) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 83 publications
2
20
0
5
Order By: Relevance
“…Acknowledging this regional bias within the literature, this synthesis of the current RCT evidence base suggests that internationally, but particularly in local Australian and New Zealand (as the definition from the Royal Australasian College of Surgeons was used for trial inclusion 18 ) General Surgery and perioperative care systems, prehabilitation interventions should only be implemented in specific patient populations, as there is unlikely to be significant benefit (particularly when considering associated time and resource investment) from additional supplementary protocols implemented across the discipline of General Surgery. 18 Although within the surgical literature even the results of sub-population meta-analyses are mixed, examples of these specific General Surgery populations where particular benefit could be found include hepatobiliary and gastrointestinal cancer surgery, where prehabilitation likely reduces length of postoperative hospital stay, 63 in particular colorectal cancer surgery where functional capacity and complication rates may be improved, 8 and bariatric surgery where body composition, functional capacity, and quality of life may be improved. 64 This systematic review adds to an evidence base that has historically found mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acknowledging this regional bias within the literature, this synthesis of the current RCT evidence base suggests that internationally, but particularly in local Australian and New Zealand (as the definition from the Royal Australasian College of Surgeons was used for trial inclusion 18 ) General Surgery and perioperative care systems, prehabilitation interventions should only be implemented in specific patient populations, as there is unlikely to be significant benefit (particularly when considering associated time and resource investment) from additional supplementary protocols implemented across the discipline of General Surgery. 18 Although within the surgical literature even the results of sub-population meta-analyses are mixed, examples of these specific General Surgery populations where particular benefit could be found include hepatobiliary and gastrointestinal cancer surgery, where prehabilitation likely reduces length of postoperative hospital stay, 63 in particular colorectal cancer surgery where functional capacity and complication rates may be improved, 8 and bariatric surgery where body composition, functional capacity, and quality of life may be improved. 64 This systematic review adds to an evidence base that has historically found mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…64 This systematic review adds to an evidence base that has historically found mixed results. [7][8][9][10][11][12][13][14][15][16][17] Past literature in colorectal cancer surgical populations has found that physical prehabilitation interventions are likely to improve functional capacity and reduce complication rates. 12 For major abdominal surgery the optimal protocol for delivery remains unclear, although if implemented effectively could reduce overall and pulmonary postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allerdings korrelieren die bisher eingesetzten Parameter nicht immer mit den postoperativen Ergebnissen. So konnte eine aktuelle Metaanalyse aus 14 Studien eine signifikante Verbesserung im 6MWT aufzeigen; ein Einfluss auf die Parameter "postoperative Komplikationsrate" und "Länge des Krankenhausaufenthaltes" blieb jedoch aus [44]. Zu ähnlichen Ergebnissen kommt auch eine aktuelle Cochrane-Analyse [45].…”
Section: Prehabilitationunclassified
“…In einer weiteren aktuell publizierten Metaanalyse wurden 14 randomisierte Studien eingeschlossen, welche Prähabilitationsprogramme bei Patienten mit kolorektalem Karzinom berücksichtigten. Hier konnten signifikante Verbesserungen in der funktionellen Kapazität, gemessen anhand des 6-Minuten-Gehtests, aber keine signifikanten Ergebnisse hinsichtlich der Krankenhausaufenthaltsdauer und der Komplikationsrate gezeigt werden 19 .…”
Section: Prähabilitation In Der Viszeralchirurgieunclassified